From Citizens Overview: Which Antecedents’ Can Assist to Increase their Satisfaction Towards the Ubiquity of Mobile Commerce Applications? - Salameh, Anas A.; Abu AlSondos, Ibrahim A.; Ali, Basel J. A.; Alsahali, Abdullah Fahad (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Recently, mobile commerce started to attract the interest of workers in the commercial sector for ease of application, where people can buy and sell items at the same time by using the internet on a mobile phone. Therefore, this research aims to investigate the extent of citizens' confidence and trust in m-commerce. The study reveals how m-commerce process over time changes the role of trading from the traditional way to the electronic one. The objective of this study is to determine the impact of trust, ease of use on satisfaction in m-commerce among citizens. Data of this research was collected from teaching staff, employees, and students and they numbered 216, the result indicates that there is a positive relationship between research model variables and that all antecedents affected citizens toward the satisfaction of m-commerce.